Surgical Management of Unilateral Horn Fracture in a Red Sokoto Buck - Zubairu Salman Abdulkadir; Abdullahi Aliyu; Haroon Ahmad Abbas; Halimat Olasubomi Lawal; Zulikha Olanrewaju Dawodu; Zulqurnain Aliyu; Qozeem Omotosho Hanafi (Journal of Applied Veterinary Science And Technology, 2026)
Background: Among the surgical conditions affecting small ruminants, fractures of unique anatomical structures such as horns are prevalent, frequently resulting in acute pain, reduced weight gain, and diminished reproductive efficiency. Inevitable culling often follows if these injuries are not promptly managed. Purpose: Described in this case report is the successful surgical management of a unilateral horn fracture in a 2 year old male Red Sokoto buck, with emphasis placed on the alleviation of complications and the critical importance of prompt intervention. Case(s): Presented to the Veterinary Teaching Hospital, University of Ilorin, was a Red Sokoto buck weighing 19 kg following a traumatic injury. Identified during clinical examination was an incomplete left horn fracture without involvement of adjacent structures. While vital parameters remained within normal limits, leucocytosis with neutrophilia was indicated by haematological analysis, suggesting a systemic response to trauma. Case Management: Achieved through xylazine sedation, local desensitization was further ensured via lidocaine infiltration of the cornual nerves. Following a circular incision at the skin horn junction, the skin was undermined to facilitate gigli wire placement; subsequently, the horn was removed, and the skin was apposed with nylon sutures. Post operative care encompassed antibiotic therapy, analgesics, and patient confinement. Uneventful healing was observed, leading to suture removal 12 days post surgery. Conclusion: Underscored by this case is the effectiveness of prompt surgical intervention in managing caprine horn fractures. Safe and favorable recovery was yielded by the implementation of dehorning with skin advancement. Critical factors in minimizing complications and safeguarding animal welfare include early detection, appropriate analgesia, and proper husbandry practices.